(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
The cases of suspended animation are reported in newspapers and on various channels of television alleging the negligence & incompetence of doctors. Present Paper is an attempt to suggest precautions for doctors to avoid such allegations.